IMPLEMENTASI AUGMENTED REALITY SEBAGAI MEDIA PROMOSI UNIVERSITAS SATYA NEGARA INDONESIA BERBASIS ANDROID MENGGUNAKAN METODE MARKER BASED TRACKING - Alfian Wahyu Prayugha; Faizal Zuli (Universitas Tridharma, 2021)
Application Augmented Reality Universitas Satya Negara Indonesia is an app that shows USNI buildings in three-dimension. The application was built on Android operating system, because Android-based smartphone has the biggest user base than others. Android-based smartphone has the biggest percentage amounting to 91.84% of users in Indonesia according to Statcounter's survey on September 2020. The goal of this app is to build an augmented-reality app as USNI's promotion media. The benefits of this research is to hopefully raise USNI's promoting activity. The method's used is marker-based tracking, in which it uses two-dimensional object marker that contains a pattern that will be read by the smartphone through the camera, usually comprises of black-and-white square illustration with thick black border and white background. The result shows that augmented reality can be applied on this app, that can be used to support the promotion. Keyword : USNI, augmented reality, marker based tracking, promotion